АВТОМАТИЗАЦИЯ СИСТЕМЫ ОБРАБОТКИ ИНФОРМАЦИИ И УПРАВЛЕНИЯ - Spiridonov N. I. (Scientific and Educational Areas Under Modern Challenges, 2022)
The use of modern computer information technologies is one of the main conditions for the effective operation of enterprises. Computers are widely used for automated information processing in science, education, industry, agriculture and other industries. In the energy sector, automated information processing and management systems operate at various levels of management of energy facilities: they collect, digitally process and store signals and processes, transmit information through various communication channels, are used in expert diagnostic systems, for modeling and decision-making
Keywords: управление; автоматизация; обработка информации; цифровые технологии; management; automation; производственные процессы; digital technologies; системы обработки информации; большой объем информации; production processes; information processing; information processing systems; a large amount of information